(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Here we are studying the quality analysis of Yamuna river in different location in India. Here testing the different parameters of water that is pH, Dissolved Oxygen (as O 2) Min, Biological Oxygen Demand (Max.) BOD, Chemical Oxygen Demand (COD), Total Dissolved Solid, Total Hardness (as CaCO 3), Calcium (as Ca), Magnesium (as Mg), Alkalinity, Conductivity, Turbidity, Total Suspended Solid and Temperature .this analysis we are doing collecting the water in different location in Yamuna rivers testing the all parameters, we are selecting some location of Yamuna river that is Goripur Yamuna , Baghpat District Magistrate, Palla Village, katha village, Sonia Vihar and Wazirabad Mandiwala Barrage. Finally, we are finding the water quality index. Water quality index must be less than 100 is more suitable in Drinking if is greater than 100it is unsuitable in drinking.